2015
DOI: 10.1016/j.marpol.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

The declining impact of piracy on maritime transport in the Indian Ocean: Statistical analysis of 5-year vessel tracking data

Abstract: a b s t r a c tThe analysis of the declining impact of piracy on maritime routes and vessel behaviours in the Indian Ocean is here performed using Long Range Identification and Tracking (LRIT) reports. A 5-year archive of vessel position data covering the period characterized by the highest number of attacks and the subsequent decline provides a unique source for data-driven statistical analysis that highlights changes in routing and sailing speeds. The work, besides demonstrating the value of LRIT data for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…), and shipping (Vespe et al. ) in this region are superimposed with emerging activities such as hydrocarbon exploration and mining (this study), and global climate change (Molinos et al. ).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…), and shipping (Vespe et al. ) in this region are superimposed with emerging activities such as hydrocarbon exploration and mining (this study), and global climate change (Molinos et al. ).…”
Section: Discussionmentioning
confidence: 72%
“…This may be because incidents of piracy off the East African coast have declined in the last 5 years and are now less of a deterrent to fishers (Vespe et al. ). Because the WIO leatherback population is critically endangered, bycatch mitigation measures in the longline industry are the first and most important management action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the imminent danger from piracy, the United Nations Security Council issued a resolution empowering foreign navies to deploy assets in the waters surrounding Somalia in a bid to reduce and remove the threat of piracy. These naval assets were tasked with the role of escorting trading vessels, monitoring fishing activities and policing the wider maritime area (Vespe, Greidanus, and Alvarez 2015). These countermeasures amongst various others from the international community have been successful in restoring a level of safe passage to the shipping routes (Vespe, Greidanus, and Alvarez 2015).…”
Section: Distribution Of Fishing Fleet Due To Piracy Activitymentioning
confidence: 99%
“…These naval assets were tasked with the role of escorting trading vessels, monitoring fishing activities and policing the wider maritime area (Vespe, Greidanus, and Alvarez 2015). These countermeasures amongst various others from the international community have been successful in restoring a level of safe passage to the shipping routes (Vespe, Greidanus, and Alvarez 2015). Chassot et al (2010) reported to the Scientific Committee of the IOTC on the influence that piracy activities were having on the dispersion of fishing fleets in the Indian Ocean, specifically in the west Indian Ocean where interactions with Somali pirates was becoming increasingly common.…”
Section: Distribution Of Fishing Fleet Due To Piracy Activitymentioning
confidence: 99%